PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 22 PADANG - Farma, Kheisa Melia (Jurnal Edukasi dan Penelitian Matematika, 2023)
If pupils lack the ability to answer problems, it will be difficult for them to meet the learning objectives for mathematics. However, class VIII pupils at SMP Negeri 22 Padang still have poor mathematics problem-solving skills. TSTS was chosen to overcome this. This type of study combines a Static Group Design research design with descriptive and quasi-experimental research. The sampling procedure employs simple random sampling. Class VIII.A is the experimental class and class VIII.B is the control class. The P-value is 0.016 (α = 0.05), meaning that H0 is rejected, so mathematical problem solving abilities are better when taught using the TSTS model than students who are taught using the conventional model.Keywords– TSTS, Mathematical Problem Solving, Conventional Learning